Propuesta de un modelo de marketing educativo para la creación de valor en el perfil competitivo del licenciado en administración de empresas de las universidades de la Región Lambayeque Perú - Pingo Jara, Roger (2008)
The countries are carrying out an outstanding list in the growth of the Peruvian economy. We observe with expectation that the universities of countries are carrying out efforts to improve the application from the marketing to their institutions and power to satisfy the necessities of their clients (family parents), consumers (students) and of the labor market whose companies and institutions demand highly competitive professionals and where the Graduate in Administration of Companies carries out an expectant list to entrepreneurship level, labor opportunities, and his contribution to the growth and managerial development and of the country, for what the central objective of the present work of doctoral investigation is: To design and to propose the application of a model of strategic educational marketing that favors the achievement of the Graduate's competitive profile in Administration of Companies in the universities of Lambayeque. For the achievement of this purpose he/she was carried out a hypothetical-deductive, descriptive investigation - analytic -, developing the process of scientific investigation with a qualitative and quantitative focus (mixed) finishing preliminary way that the application in the universities of a model of strategic educational marketing favors in a significant way the achievement of the Graduate's competitive profile in Administration of Companies.